Fabrication and environmental assessment of photo-assisted Fenton-like Fe/FBC catalyst utilizing mealworm frass waste. (20th May 2020) - He, Lei; Yang, Shan-Shan; Bai, Shun-Wen; Pang, Ji-Wei; Liu, Guo-Shuai; Cao, Guang-Li; Zhao, Lei; Feng, Xiao-Chi; Ren, Nan-Qi
Abstract: The massive generation of dye wastewater and mealworm waste has shown potential dangers. In this study, an innovative method was developed to fabricate an efficient photo-assisted Fenton-like heterogeneous catalyst, namely, iron (Fe)-loaded mealworms (the larvae of Tenebrio molitor Linnaeus) frass-based biochar (Fe/FBC). The physico–chemical properties were characterized by X-ray powder diffraction, scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, Brunsuer-Emmett-Teller, Raman spectroscopy, inductively coupled plasma spectroscopy, and N2 sorption-desorption isotherms. The results revealed the successful loading of Fe(III) on Fe/FBC surface with a loaded content of 6.0 wt%, and increased graphitization degree with high surface area (90.65 m 2  g −1 ) appeared in Fe/FBC. Excellent removal efficiency toward malachite green (MG) dye (67% TOC within 5 min) and good recycling performance of Fe/FBC were observed in photo-assisted heterogeneous Fenton-like system, indicating that the aid of light irradiation may accelerate the heterogeneous Fenton-like reaction and realize the synergistic effect of enhanced MG degradation. Three key possible MG degradation pathways, involving N-de-methylation, hydroxylation, and destruction of the conjugated chromophore, were proposed based on the results of ultra-performance liquid chromatography-tandem mass spectrometry. Life cycle assessment study was applied to evaluate the environmental impacts of the following two disposal strategies for frass wastes: Fe/FBC catalyst facilitation (scenario A) and composting treatment (scenario B) at midpoint level. Regarding ten impact categories, scenario A produced lower environmental footprint compared to scenario B, indicating that the facilitation of Fe/FBC is a financially and environmentally viable strategy for relieving the greenhouse effect, energy crisis, water toxicity, and eutrophication. Graphical abstract: Image 1 Highlights: Mealworm frass waste was used to fabricate a photo-assisted Fenton-like catalyst. Fe/FBC showed prominent degradation capacity, good reusability and stability. Photo-assisted Fenton-like degradation of MG and reaction mechanism were studied. LCA was applied to evaluate environmental impacts of two frass disposal scenarios. Fe/FBC facilitation was an environmentally viable strategy.